2007
DOI: 10.1002/pssb.200675126
|View full text |Cite
|
Sign up to set email alerts
|

ZnO:Mn:Cu nanowires prepared by template method

Abstract: Manganese and copper doped ZnO films and nanowire arrays were prepared by cathodic electrodeposition from aqueous solution. The electrochemical process was examined by linear voltammetry and the morphology and the composition of obtained semiconductor were observed by SEM and EDX measurements. Optical absorption spectra indicated the presence of copper in ZnO : Mn : Cu nanowire arrays as Cu 2+ ions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 14 publications
1
33
0
Order By: Relevance
“…Switzer [13] showed that Cu 2 O can be obtained at the working electrode at pH = 9-12. Our optical measurements [6] proved the presence in a ZnO : Mn : Cu film of both cupric and cuprous oxides; therefore, we consider that a part of Cu 2+ ions from solution can be precipitated together with Zn 2+ and Mn 2+ ions, taking into account the small values for solubility products of the formed hydroxides.…”
Section: Voltammetric Characterization Of Doped Zno Electrodepositionsupporting
confidence: 53%
See 1 more Smart Citation
“…Switzer [13] showed that Cu 2 O can be obtained at the working electrode at pH = 9-12. Our optical measurements [6] proved the presence in a ZnO : Mn : Cu film of both cupric and cuprous oxides; therefore, we consider that a part of Cu 2+ ions from solution can be precipitated together with Zn 2+ and Mn 2+ ions, taking into account the small values for solubility products of the formed hydroxides.…”
Section: Voltammetric Characterization Of Doped Zno Electrodepositionsupporting
confidence: 53%
“…[1 -5] The electrochemical deposition was employed for preparation of Mn-and Cu-doped ZnO semiconductor both as a film on the platinum electrode and as nanowire arrays in the polycarbonate membrane. [6] The template method for electrosynthesis of semiconductor nanowires involves the deposition of a metal thin film on one side of the membrane.…”
Section: Introductionmentioning
confidence: 99%
“…Though a wide research has been done on doped nanostructured materials, there are few reports on doped ZnO nanostructures, particularly about their optical properties. The transition metal doped nanostructure is an effective method to adjust the energy levels and surface states of ZnO, which can further introduce changes in its physical and especially optical properties [12] . In addition to the UV excitonic emission peak, ZnO commonly exhibits the visible luminescence at different emission wavelengths due to the intrinsic or extrinsic defects [13] .…”
mentioning
confidence: 99%
“…For semiconductors, doping is a powerful tool to tailor the electrical and optical properties. The doping of transition metals (TM) offers feasible means of tuning physical properties, especially optical, electrical and magnetic properties to suit specific needs and applications [5]. The most commonly used metallic dopants are Cr- [6], Co- [7], Cu- [8], Mn- [9] doped ZnO systems.…”
Section: Introductionmentioning
confidence: 99%